Recycling Of Peneapple Waste Using Lactobacillus Delbroeckii to Lactic Acid - Abdullah Abdullah; H. B. Mat (Dept. of Chemical Engineering, Diponegoro University, 2001)
The liquid pineapple waste contain mainly sucrose, glucose, fructose, and other nutrients. It therefore can potentiall be used as carbon source for organic acid fermentation. Recently, lactic acid has been considered to be an important raw material for production of biodegradadable lactace polymer. The experiments weree carried out in shake flash fermentation using lactobacillus delbroeckii. Effect of some parameters such as temperature, initial Ph, initial substrate concentration, yeast extract concentration and fermentation time to the yield have been studied. The highest yield was 85.65% achieved at 40 0C, PH 6.00, 52.2 g/l sugar concentration with 5 g/l yeast extract. There was no significant increasing in lactic acid production was observed if supplementation of yeast extract above 10%.Keyword : lactic acid fermentation, liquid pineapple waste, lactobacillus delbrueckii